Life & philosophy of Mahamahopadhyaya Gopinath Kaviraj : papers presented at the seminar - Kaviraj, Gopi Nath (University of Calcutta, 1981)
Volume commemorating Gopi Nath Kaviraj, 1887-1976, Indologist; comprises papers, on his life and works and Indic philosophy, presented at the Seminar on the Life and Philosophy of Mahamahopadhyaya Gopinath Kaviraj, Calcutta, India, 1978.